Efecto de los antitranspirantes sobre el crecimiento y producción del sorgo de grano - Kuganathan, A; Palaniappan, S (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Field experiments were conducted at Tamil Nadu Agricultural University, Coimbatore, India during the summer and monsoon seasons of 1977 on grain sorghum (CSH 5) under the conditions of limited water supply. The results revealed that antitranspirants significantly increased the number of effective leaves, LAI at flowering and advanceds the days to fifty per cent flowering by 2 to 3 days. Antitranspirants also had significant influence on number of panicles emerged per plot, number of rachii per earhead, size of the earhead and thousand grain weight. During later stages of crop growth, antitranspirants tended to induce the senescence of older leaves. Grain yield was increased by 12 per cent on an average in the monsoon season. Dry matter production was also increased significantly by about 8 per cent over control. Antitranspirants had no adverse effects on photosynthesis. Application at 45 days after sowing was most effective.